(untitled) (KULT_online, 2022)
The Routledge Companion to Sexuality and Colonialism, edited by Dagmar Herzog and Chelsea Schields, convinces with its various contributions about the history and the entanglements of sexuality and colonialism. The contributions cover a broad range, both in terms of the time and spaces investigated as well as in terms of the methodological approaches and the analyzed sources.